2013
DOI: 10.3389/fncel.2013.00175
|View full text |Cite
|
Sign up to set email alerts
|

Comparative neuronal differentiation of self-renewing neural progenitor cell lines obtained from human induced pluripotent stem cells

Abstract: Most human neuronal disorders are associated with genetic alterations that cause defects in neuronal development and induce precocious neurodegeneration. In order to fully characterize the molecular mechanisms underlying the onset of these devastating diseases, it is important to establish in vitro models able to recapitulate the human pathology as closely as possible. Here we compared three different differentiation protocols for obtaining functional neurons from human induced pluripotent stem cells (hiPSCs):… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 53 publications
(59 reference statements)
4
29
0
Order By: Relevance
“…As previously reported (34), iPSC- were relatively immature at 10 weeks in culture (Figure 5). Qualitative analysis suggested that iPSC-neurons bearing the 15q11.2(BP1-BP2) deletion had altered dendritic morphology (Figure 5).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As previously reported (34), iPSC- were relatively immature at 10 weeks in culture (Figure 5). Qualitative analysis suggested that iPSC-neurons bearing the 15q11.2(BP1-BP2) deletion had altered dendritic morphology (Figure 5).…”
Section: Resultssupporting
confidence: 87%
“…PSD-95 labeling showed a punctate staining in iPSC-neurons from a control individual, similar to observed in postmortem human studies (38). In addition, consistent with other iPSC studies, PSD-95 appeared to be more diffuse in neurites which may represent relative immaturity in the iPSC-neurons (34). To test this possibility, further agnostic, unbiased analyses of dendritic architecture are needed in iPSC-neurons differentiated for longer periods.…”
Section: Discussionsupporting
confidence: 89%
“…As primary neurons have been shown to facilitate the maturation of iPSC-derived neurons (Weick et al 2011;Verpelli et al 2013;Su et al 2015), we cultured iPSC-derived hNPCs together with primary rat cortical neurons. To identify iPSC-differentiated neurons among the co-culture system, we selectively expressed a fluorescent protein, tdTomato, behind a neuron-specific Synapsin 1 (Syn1) promoter in the hNPCs.…”
Section: Morphological and Functional Analysis Of Ipscdifferentiatedmentioning
confidence: 99%
“…Dermal fibroblasts of a healthy, ethnically matched donor and their iPSCs derivatives were previously described by us. 18 Fibroblasts were cultured at 37 °C in a 5% CO 2 in E-MEM supplemented with 15% heat-inactivated FCS, 100 units/ml penicillin, 100  μ g/ml streptomycin, 100  μ M non-essential amino acids and 2 mM glutamine. Primary MEFs (PMEF-CFL, Millipore, Bedford, MA, USA) were cultured in DMEM/F12 supplemented with 20% heat-inactivated FCS, 100 units/ml penicillin, 100  μ g/ml streptomycin, 100  μ M non-essential amino acids and 2 mM glutamine.…”
Section: Methodsmentioning
confidence: 99%